Challenges for the management of basic and middle education institutions - Sánchez-Buitrago, Jorge Oswaldo
This work systematizes the challenges related to educational management in official elementary and middle school educational institutions in the district of Santa Marta. The research was conceived from the qualitative nature with multiple case studies. As the main instrument for the collection of information, in-depth interviews with teachers and teacher directors of 12 targeted district educational institutions were used, additionally a documentary analysis of the institutional educational projects (PEI) was carried out. The challenges are presented according to the four areas of educational management proposed by the Ministry of National Education (MEN): directive management, academic management, administrative and financial management, and community management. The challenges identified contribute to the understanding of the problems of educational quality present in the district of Santa Marta, as an initial stage to promote educational transformation in the territory, through the proposal of pedagogical routes for institutional improvement.